2017
DOI: 10.20448/2002.11.19.23
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Continuous Auditing for the Public Sector in Nigeria

Abstract: Aims: The main purpose of the study was to access the challenges the government financial system in Nigeria has undergone in the recent times and with the aim of proposing a model that could be used to implement continuous auditing by the Public Sector Audit Organizations. Study design: Adoption of existing model and survey using questionnaires. Place and Duration of Study: Nigeria, 2014.Methodology: The existing continuous auditing models were studied and the integrated Continuous Auditing, Monitoring and Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The analysis for descriptive statistics show that there are about 10% of executive turnover events has occurred during the sampling period. And the percentage value is slightly consistent with two studies in the US which reported at 13% and 10% respectively (Coughlan andSchmidt, 1985 andMehran andYermack, 1997;Orumwense, 2017). The result illustrated in Table 1 shows the sample selection firms based the board listing and its sectors classification as the majority of listed firms with equity plan provided for executives are from regulated market.…”
Section: Study's Findings and Discussionsupporting
confidence: 85%
“…The analysis for descriptive statistics show that there are about 10% of executive turnover events has occurred during the sampling period. And the percentage value is slightly consistent with two studies in the US which reported at 13% and 10% respectively (Coughlan andSchmidt, 1985 andMehran andYermack, 1997;Orumwense, 2017). The result illustrated in Table 1 shows the sample selection firms based the board listing and its sectors classification as the majority of listed firms with equity plan provided for executives are from regulated market.…”
Section: Study's Findings and Discussionsupporting
confidence: 85%
“…The main reasons quoted for that are governance complexities, cyber is everything (data protection, cybersecurity considerations, staff training), full transparency, reporting on steroids, and skillset shortages [7]. The authors in [8,9,10] have described requirements and problems for the introduction of continuous auditing in Nigeria, Malaysia, and the UK, but no ready used AI platform, or conceptual models, or concrete implementation or evaluations in the literature to date.…”
Section: Related Workmentioning
confidence: 99%
“…The existing literature has shown that foreign capital inflows are volatile and pro-cyclical and is declines during crisis times. These patterns have more intensity in the countries having different income levels and are also referred to -sudden stops‖ that refers to immense collapses in capital inflows that subsequently brings crises (Georgiadis, 2016;Orumwense, 2017).…”
Section: Introductionmentioning
confidence: 99%